Cost analysis of health workforce investments for COVID-19 response in Ghana. (19th May 2022) - Asamani, James Avoka; Ismaila, Hamza; Okoroafor, Sunny C.; Frimpong, Kingsley Addai; Oduro-Mensah, Ebenezer; Chebere, Margaret; Ahmat, Adam; Nabyonga-Orem, Juliet; Christmals, Christmal Dela; Nyoni, Jennifer; Kuma-Aboagye, Patrick
Abstract : The COVID-19 pandemic had multiple adverse impacts on the health workforce that constrained their capacity to contain and combat the disease. To mitigate the impact of the pandemic on the Ghanaian health workforce, the government implemented a strategy to recruit qualified but unemployed health workers to fill staffing gaps and incentivise all public sector health workers. This paper estimated the cost of the new recruitments and incentives given to health workers and presented lessons for health workforce planning in future health emergencies towards health systems resilience. Between March and November 2020, 45 107 health workers were recruited, representing a 35% boost in the public sector health workforce capacity, and an increase in the recurrent public health sector wage bill by about GHS103 229 420 (US17 798 176) per month, and about GHS1.24 billion (US213.58 million) per annum. To incentivise the health workforce, the government announced a waiver of personal income taxes for all health workers in the public sector from April to December 2020 and offered a 50% additional allowance to some health workers. We estimate that the Government of Ghana spent about GH¢16.93 million (equivalent to US2.92 million) monthly as COVID-19 response incentives, which translates into US35 million by the end of 2020. Ghana invested considerably in health workforce recruitment and incentives to respond to the COVID-19 pandemic, resulting in an almost 37% increase in the public sector wage bill. Strengthening investments in decent employment, protection and safety for the health workforce using the various resources are helpful in addressing future pandemics.